2020
DOI: 10.1177/1098612x19895081
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin D status in sick cats with and without cholestatic liver disease

Abstract: Objectives Vitamin D deficiency accompanies chronic cholestatic liver disease (CLD) in humans. The vitamin D status of cats with CLD is unknown. The objectives of this study were to describe serum vitamin D concentrations in cats with CLD and to determine if they correlated with indices of liver disease severity. Methods Thirty-six cats with CLD, defined by increases in serum bilirubin and serum alanine aminotransferase, and 23 sick cats with non-hepatobiliary diseases were prospectively enrolled. Serum 25-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
(148 reference statements)
0
5
0
Order By: Relevance
“…Low vitamin D status has been reported in cats and dogs with gastrointestinal disorders (compared to healthy controls), especially in dogs with a protein-losing enteropathy (PLE) (Mellanby et al 2005b, Gow et al 2011, Lalor et al 2014, as well as dogs with exocrine pancreatic insufficiency (EPI) (Barko & Williams 2018) acute pancreatitis (Kim et al 2017) and both dogs and cats with liver disease (Schulze et al 2000, Kibler et al 2020.…”
Section: Acquired Vitamin D Disorders -Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Low vitamin D status has been reported in cats and dogs with gastrointestinal disorders (compared to healthy controls), especially in dogs with a protein-losing enteropathy (PLE) (Mellanby et al 2005b, Gow et al 2011, Lalor et al 2014, as well as dogs with exocrine pancreatic insufficiency (EPI) (Barko & Williams 2018) acute pancreatitis (Kim et al 2017) and both dogs and cats with liver disease (Schulze et al 2000, Kibler et al 2020.…”
Section: Acquired Vitamin D Disorders -Deficiencymentioning
confidence: 99%
“…Vitamin D deficiency and rickets has occasionally been reported in dogs with liver diseases likely as a consequence of impaired intestinal absorption of vitamin D (Schulze et al 2000). Additionally, many cats with cholestatic liver disease, especially hepatic lipidosis, had suboptimal serum 25(OH)D levels, although the clinical importance of this remains uncertain given that that ionised calcium concentrations remained normal (Kibler et al 2020).…”
Section: Vitamin D Metabolism and Disordersmentioning
confidence: 99%
“…1 Cats with inflammatory bowel disease, intestinal small cell lymphoma, cholestatic liver disease, feline immunodeficiency virus and infections have been found to have low levels of serum vitamin D concentrations, as measured by serum calcidiol. 35 In a study looking at vitamin D status in cats with cardiomyopathy, researchers found that age played an important negative relationship with vitamin D status. 6…”
Section: Introductionmentioning
confidence: 99%
“…1 Cats with inflammatory bowel disease, intestinal small cell lymphoma, cholestatic liver disease, feline immunodeficiency virus and infections have been found to have low levels of serum vitamin D concentrations, as measured by serum calcidiol. [3][4][5] In a study looking at vitamin D status in cats with cardiomyopathy, researchers found that age played an important negative relationship with vitamin D status. 6 Calcidiol, in the form of 25-hydroxycholecalciferol (25[OH]D 3 ), has been shown to be more potent and effective than cholecalciferol (D 3 ) in raising vitamin D status in humans when ingested.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dogs that died from acute pancreatitis were found to be more deficient than those that survived the crisis, indicating a role for this vitamin as a prognostic marker during pancreatitis (Kim et al, 2017). In cats with cholestatic disease, serum concentration of vitamin D was identical when compared to felines sick from different systemic causes (Kibler et al, 2020).…”
Section: Resultsmentioning
confidence: 99%